PENGARUH PROFITABILITAS, KESEMPATAN INVESTASI DAN LIKUIDITAS TERHADAP KEBIJAKAN DIVIDEN (PADA PERUSAHAAN LQ45 YANG TERGABUNG DALAM BURSA EFEK PERIODE 2010-2013) - admin, YUVENSIA YUVENSIA B11111064 (Jurnal Manajemen Update, 2016)
This research aims to analyze the influence of profitability, invesment opportunity setand liquidity of the dividend dplicy (DPR) in LQ45 companies which are listed in IndonesianStock Exchange in the year 2010 until 2013. This research uses secondary data which wasused in the form of financial statements samples obtained from the IDX. This research usedpurposive sampling, data collection have been done by specifying the criteria for determiningsampel resulting in 16 LQ45 companies during the 4 years of observation. The hypotheseswere tested using multiple linear regression analysis model. Based on the results of studiesusing multiple linear regression analysis model showed that the profitability and liquidityhas positive affect on the dividend policy (DPR), but the investment opportunity has apositve significant influence on the dividend policy (DPR). Third independent variables justcan explain dividend payout ratio of 18%.Key words: dividend policy (DPR)